ANALISIS PROSES KOGNITIF PEMBELAJARAN TAHFIDZ AL-QUR’AN DALAM PEMBENTUKAN KARAKTER RELIGIUS SANTRI PONDOK PESANTREN AL-MIZAN - Andis Suha Fadhilah; Abdul Malik Karim Amrullah; Muh. Hambali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the cognitive process in Tahfidz Al-Quran learning and its implications for the formation of students' religious character at Pondok Pesantren Al-Mizan Muhammadiyah Lamongan. The main focus of this study lies in how time management and memorization methods are systematically managed through the perspective of cognitive learning theory. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that the implementation of tahfidz at Al-Mizan applies a